Náhrada kyčelního kloubu MIS-AL technikou - roční výsledky - Stehlík, Jiří; Musil, David; Held, Martin; Stárek, Martin (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2008)
To present a prospective evaluation of one-year results in 162 patients undergoing total hip arthroplasty from a minimally invasive antero-lateral approach (THA MIS-AL). MATERIAL: A total of 249 THA MIS-AL procedures were performed between January 2005 and October 2007. At one year after surgery 162 patients were examined and their conditions evaluated by the Harris score, percent satisfaction assessment, 1-to-5 scale school marking, findings on lateral X-ray images and occurrence of post-operative complications. METHODS: With the patient lying in a lateral recumbent position, access is gained through a short incision (5 to 8 cm) along a line connecting the greater trochanter and the anterior superior iliac spine, between the gluteus medius and tensor fasciae latae muscles. After the articular capsule is removed and neck osteotomy done by a two-step procedures, the head is extracted. Both the acetabulum and the femur are processed with special instruments and a cemented or a cementless implant is inserted. Standard prophylaxis with antibiotics and anticoagulants is administered. The patient is mobilized from the second post-operative day, with individually allowed, partial weight-bearing of the operated extremity. RESULTS: In the 162 evaluated patients, the average Harris score increased from pre-operative 46.8 to post-operative 90.4 points. Excellent and good outcomes were found in 84% of the patients. The average school marking was 1.12 and patient satisfaction expressed in percent was 97%. Of 32 patients who had undergone both standard and minimally invasive hip replacement surgery, 25 considered the MIS AL technique to be better, five found no difference and two regarded is as worse. In two patients (0.8%), exposure had to be extended by the standard antero-lateral approach because of femur damage without displacement.Two patients (0.8%) suffered temporary post-operative peroneal nerve paresis. One patient (0.4%) had functional complications and five (2%) had to undergo surgery for haematoma. Sockets in a position other than the optimal 35 degrees to 55 degrees were recorded in two patients. The stem showed a 5 degrees varus deviation in one patient and that of 4 degrees in eight patients; a 4 degrees valgus deformity was found in three patients. Para-articular ossifications (stage 1 or 2) not affecting joint function were recorded in 20 patients (12%). DISCUSSION: Our results show good subjective evaluation of this technique. Its advantages include less pain and earlier patient mobilization. In our first patients a higher number of slight stem malposition (up to 3 degrees) was recorded. Early complications were rare. The occurrence of paraarticular ossifications was an unexpected finding; these, however, did not influence either joint function or subjective evaluation of the outcome. CONCLUSION: If all indication criteria are met and the operative technique is well mastered, the MIS-AL procedure helps provide successful outcomes with less muscle damage and more rapid rehabilitation for people receiving hip replacement; it has few complications and, in indicated cases, it appears to be an approach preferable to the standard THA technique.
Keywords: ženské pohlaví; Minimally Invasive Surgical Procedures; Female; Aged, 80 and over; senioři nad 80 let; náhrada kyčelního kloubu; lidé; Aged; lidé středního věku; Adult; Arthroplasty, Replacement, Hip; Male; Middle Aged; mužské pohlaví; dospělí; Humans; miniinvazivní chirurgické výkony; senioři